Rapport femme-forêt : vers un écoféminisme de la complexité - Marie Nicole Taha Nkoum (VertigO)
Environmental degradation is one of the most crucial issues of the moment, and the mechanisms and strategies to contain it still give rise to a number of heated debates. One of the preferred approaches to curb this phenomenon therefore remains the resilience that allows degraded ecosystems to regain relatively their initial ecological integrity. However, the contribution of women, who are among the most vulnerable and most affected by this degradation, is still poorly documented and therefore very poorly valued. The great majority of scientific productions within the interfaces between feminism and ecology, although they are constructive, remain very tainted by a sort of battle of dualism, common to a certain scientific discourse, the method of which seems to us somewhat outdated. Eroding the very basis of the immense contribution of these scientific approaches to the question. It therefore seems urgent and pertinent to capitalize these contributions in a single approach based on a reflection of complex thought and its place in the interface between feminism and ecology, an approach that we will refer to here as "ecofeminism of complexity". This proposal Seems to us all the more relevant in that it will make it possible to define a platform for the valorisation and capitalization of women's initiatives for the positive transformation of ecosystems, in this case (for the purposes of this article) the resilience experience of women market gardeners of the Mbao classified forest in the Dakar suburbs of Senegal.